Female Emancipation and the sixty fashion of three visionaries: Pierre Cardin, André Courrèges and Paco Rabanne (ModaPalavra e-periódico, 2023)
This work exposes how stylists’ aesthetic productions, entitled: the three visionaries, legitimized the 1960’s fashion decade or appearance regime, and how they, in line with the historical context of the time, acted as agents in the process of female emancipation, the from the concept of Visual Discourse of Lopes, M.T. (2014). We talk about how fashion aroused the processes of women’s emancipation, also highlighting the change in the line of modesty with the use of the mini essay, expanding this aspect to an understanding of it as a struggle for the will to truth (Foucault [(1970)) 203)] that empowered women and the female body of that period.
Keywords: female emancipation; visual discourse; fashion - 1960